Caffeoylquinic Acids, Cytotoxic, Antioxidant, Acetylcholinesterase and Tyrosinase Enzyme Inhibitory Activities of Six Inula Species from Bulgaria. Issue 4 (18th March 2020) - Trendafilova, Antoaneta; Ivanova, Victoria; Rangelov, Miroslav; Todorova, Milka; Ozek, Gulmira; Yur, Suleyman; Ozek, Temel; Aneva, Ina; Veleva, Ralitza; Moskova‐Doumanova, Veselina; Doumanov, Jordan; Topouzova‐Hristova, Tanya
Abstract: Chlorogenic (5‐CQA), 1, 5‐, 3, 5‐, 4, 5‐ and 3, 4‐dicaffeoylquinic (DCQA) acids were identified and quantified in the methanol extracts of Inula oculus‐christi L., I. bifrons L., I. aschersoniana Janka var. aschersoniana, I. ensifolia L., I. conyza (Griess .) DC. and I. germanica L. by HPLC analysis. The amount of 5‐CQA varied from 5.48 to 28.44 mg/g DE and the highest content was detected in I. ensifolia . 1, 5‐DCQA (4.05–55.25 mg/g DE) was the most abundant dicaffeoyl ester of quinic acid followed by 3, 5‐DCQA, 4, 5‐DCQA and 3, 4‐DCQA. The extract of I. ensifolia showed the highest total phenolic content (119.92±0.95 mg GAE/g DE) and exhibited the strongest DPPH radical scavenging activity (69.41±0.55 %). I. bifrons extract was found to be the most active sample against ABTS .+ (TEAC 0.257±0.012 mg/mL) and the best tyrosinase inhibitor. The studied extracts demonstrated a low inhibitory effect towards acetylcholinesterase and possessed low cytotoxicity in concentration range from 10 to 300 μg/mL toward non‐cancer (MDCK II) and cancer (A 549) cells. Abstract :